Understanding Consumers’ Purchase Behavior and Brand Trust in Bangladesh’s Live-Streaming E-Commerce - Md Ibrahim Miah (Future Science / FSH-PH Publications, 2026)
Live-streaming e-commerce is growing very quickly in the Bangladesh market. It combines entertainment, real-time audience interaction, and instant purchasing. Interested consumers can watch product details, ask questions and buy products during live sessions. This shopping format is becoming popular because it offers a personal feel and is highly interactive. Trust and communication play a strong role in this type of Live-streaming. However, academic research on live-streaming commerce in Bangladesh is still limited. This study examines how live-streaming e-commerce affects purchase behaviour and builds brand trust. It focuses on real-time features for engagement, such as live chat, audience comments, Q&A sessions, and time-bound offers. The study also examines how customers and live streamers interact regarding perceived authenticity and para-social ties. During live shopping events, these elements are anticipated to influence trust and purchase decisions. A quantitative research design was used. Data were collected from 400 consumers in Bangladesh who had prior experience with live-streaming shopping. The survey measured real-time engagement, brand trust, and purchase behavior. The data were analyzed using correlation and regression analyses and structural equation modelling. The results show that real-time interaction strongly influences consumer purchase behavior. Active engagement makes an emotional involvement and urgency. Brand trust also positively affects purchase behaviour. This study contributes to the understanding of live-streaming e-commerce in an emerging market. It offers practical insights for digital marketers, e-commerce entrepreneurs and platform designers.